Access to urban parks: Comparing spatial accessibility measures using three GIS-based approaches. (November 2021) - Wang, Siqin; Wang, Mingshu; Liu, Yan
Abstract: Urban parks are essential components of urban ecosystems, providing recreation and relaxation places to residents. Measuring the spatial accessibility to urban parks serves as an initial step in urban planning and developing urban development strategies to improve social and environmental justice. This study aims to evaluate measures of spatial accessibility to urban parks by comparing three geographic information systems (GIS)-based approaches, accounting for network complexity, transport modes, distance thresholds, and destination choices. Taking Ipswich City (Australia) and Enschede (the Netherlands) as two testbeds, we examine the spatial patterns of a total of 21 accessibility measures in the two cities and conduct a correlation and principal component analysis to unravel the interrelationship between these measures. The results suggest that among all measures under the three approaches, the selection of distance thresholds and transport modes matter more to accessibility measures than the destination choices. Furthermore, when distance threshold and transport mode are held constant, the network-based and entrance-based methods provide more realistic accessibility measures than other methods. We also discuss the generality of the entrance-based method we propose and suggest ways to choose the most appropriate accessibility measure for use in different contexts. Highlights: Three GIS-based approaches are proposed to measure park accessibility, with distinctive outcomes. Network complexity, transport mode, distance threshold, and destination choice are used to measure park accessibility. The selection of a distance threshold and a transport mode matter more than the choice of destinations. Using network and entrance-based method generates more realistic accessibility measures than other methods. The network and entrance-based method can be applied to measure park accessibility in different geographic contexts.